Effect of Investment Banking on Innovation and Growth of Start-UPS - Segun Kehinde; Chinonye Moses; Borishade Taiye; Kehinde Oladele; Busola Simon-Ilogho; Kemi Kehinde (International Journal of Educational Technology Research, 2023)
The impact of investment banking on start-up growth and innovation is examined in this paper. We conduct a review of the literature to find out what research has already been done on the benefits of investment banking for startups in terms of facilitating access to capital, offering advisory services, and enhancing reputation and visibility. Investment banking, according to our research, can have a positive impact on start-ups' innovation activities, such as patenting, spending on R&D, and product development, as well as on their growth outcomes, such as revenue, profitability, and market valuation. To address the gaps and restrictions in the current literature, we offer some directions for future research.